Caribou Use of Habitat Near Energy Development in Arctic Alaska. Issue 3 (18th December 2019) - Johnson, Heather E.; Golden, Trevor S.; Adams, Layne G.; Gustine, David D.; Lenart, Elizabeth A.
Abstract : Despite the long‐term presence of energy development within the summer range of the Central Arctic Caribou Herd, we found that female caribou reduced their use of habitat near infrastructure during all the time periods we examined, although the effects waned across the summer. Given our findings, minimizing the influence of energy development on caribou behavior may be accomplished by reducing the overall footprint of development within key seasonal habitat areas and movement corridors. ABSTRACT: Increasing demands for energy have generated interest in expanding oil and gas production on the North Slope of Alaska, USA, raising questions about the resilience of barren‐ground caribou ( Rangifer tarandus ) populations to new development. Although the amount of habitat lost directly to energy development in the Arctic will likely be relatively small, there are significant concerns about habitat that may be indirectly affected because of caribou avoidance behaviors. Behavioral responses to energy development for wildlife have been documented, but such responses are often assumed to dissipate over time, despite scant information on the ability of animals to habituate. To understand the long‐term effects of energy development on barren‐ground caribou, we investigated the behavior of the Central Arctic Herd in northern Alaska, which has been exposed to oil development on its summer range for approximately 40 years. Using recent (2015–2017) location data from global positioning system (GPS)‐collared females, we conducted a zone of influence analysis to assess whether caribou reduced their use of habitat near energy development, and if so, the distance the effects attenuated. We conducted this analysis for the calving, post‐calving, and mosquito harassment periods when caribou exhibit distinct resource selection patterns, and contrasted our results to past research that investigated the responses of the Central Arctic Herd immediately following the construction of the oil fields. Despite the long‐term presence of energy development within the Central Arctic Herd summer range, we found that female caribou exhibited avoidance responses to infrastructure during all time periods, although the effects waned across the summer. Caribou reduced their use of habitat within 5 km of development during the calving period, within 2 km during the post‐calving period, and within 1 km during the mosquito harassment period; these areas were predicted to overlap 12%, 15%, and 17% of important calving, post‐calving, and mosquito period habitat, respectively. During the calving period, the indirect effects we observed were similar to those observed in past research, whereas during the post‐calving and mosquito periods, we detected avoidance responses that had not been previously reported. These findings corroborate a growing body of evidence suggesting that habituation to industrial development in caribou in the Arctic is likely to be weak or absent, and emphasizes the value of minimizing the footprint of infrastructure within important seasonal habitat to reduce behavioral effects to barren‐ground caribou. © 2019 The Authors. The Journal of Wildlife Management published by Wiley Periodicals, Inc. on behalf of The Wildlife Society.